National Planning Committee - Planning Commission (Planning Commission, 1939)
The Proceedings of the National Planning Committee (1938–1939) present an early and comprehensive vision for India’s socio-economic transformation through planned development. The committee emphasized poverty alleviation, employment generation, and industrialization grounded in social justice and economic equity. Its recommendations covered agricultural reforms, promotion of key, medium, and cottage industries, labor rights, progressive taxation, and reduced military expenditure in favor of social development. Special focus was placed on self-sufficiency through efficient use of indigenous resources, quality control, standardization, and scientific research. The establishment of subcommittees, coordination among provinces, and the integration of expert knowledge underscored the NPC’s systematic approach. Overall, the proceedings reflect a foundational effort to design a national planning framework aimed at equitable growth, industrial self-reliance, and improved living standards in India.
Being an abstract of Proceedings and other particulars relating to the National Planning Committee
National Planning Committee
Keywords: National Planning Committee; Economic Planning; Industrial Development; Agricultural Reform; Labor Rights; Social Justice; Self-Reliance; Industrialization Strategy; Standardization and Quality Control; Provincial Coordination; Public Utilities; Planned Economy